Therapies for Parkinson’s disease and the gut microbiome: evidence for bidirectional connection - Hey, Grace; Nair, Navya; Klann, Emily; Gurrala, Anjela; Safarpour, Delaram; Mai, Volker; Ramirez-Zamora, Adolfo; Vedam-Mai, Vinata (Frontiers in Aging Neuroscience, 2023)
The gut brain axis (GBA), a bidirectional communication pathway has often been linked to health and disease, and gut microbiota (GM), a key component of this pathway shown to be altered in Parkinson’s disease (PD), are suggested to contribute to the pathogenesis of PD. There are some studies that report the impact of oral medication therapy on GM, however, there are even fewer studies that discuss the impact of other treatments such as device assisted therapies (DAT) including deep brain stimulation (DBS), levodopa-carbidopa intestinal gel infusion (LCIG) and photobiomodulation (PBM) and how these might impact GM. Here, we review the literature and summarize findings of the potential contributions of GM to the heterogenous clinical response to pharmaceutical therapies among individuals with PD. We also discuss the potential interactions between the GM and DATs such as DBS and LCIG and present evidence for alterations in GM in response to DATs. Given the complexity and highly individual nature of the GM of patients with PD and the potential influence that other external factors such as diet, lifestyle, medications, stage of the disease and other comorbidities, further investigations into the response of GM to therapies are worthy of further study in prospective, controlled trials as well as medication naïve individuals. Such detailed studies will help us further comprehend the relationship between GM in PD patients, and will help investigate the potential of targeting GM associated changes as a treatment avenue for PD.